Crop wild relatives in the protected areas of the Republic of Bashkortostan - S. R. Miftakhova; L. M. Abramova; N. M. Saifullina; O. V. Yusupova (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. Comprehensive research into crop wild relatives (CWR) is essential to ensure food security. Protected areas serve as the main reserves for CWR in situ conservation and their population genetics studies. There are four federal protected areas in the Republic of Bashkortostan: the Bashkiria National Park, the Shulgan-Tash State Biosphere Nature Reserve, the South Ural and Bashkir State Nature Reserves.Materials and methods. The floristic study of CWR was conducted using the standard route method. The methods of comparative floristics were applied in the CWR analysis,. The economic value of plant species was assessed according to the ranking developed at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources.Results. In total, out of 259 species of CWR growing in Bashkortostan, 186 (72%) occur in the federal protected areas, with the highest number in the Bashkiria National Park (148 spp.). Species belonging to the Poaceae, Fabaceae, Rosaceae and Lamiaceae families and the Poa L., Trifolium L., Lathyrus L., Allium L. genera are predominant. CWR are mainly confined to the forest meadow, forest margin, steppe and riverside communities. Alpine and raised bog CWR species occur only in the South-Ural Nature Reserve. There are 13 regional endemics in the studied territories and 34 species on their range boundaries. Of the 23 CWR species listed in the regional Red Book, seven are conserved in the surveyed areas: Allium obliquum L., Crambe tataria Sebeok, Linum uralense Juz., Melilotoides platycarpos (L.) Soják, Oxycoccus microcarpus Turcz. ex Rupr., Rubus arcticus L., and R. humulifolius C.A. Mey.Conclusion. Monitoring of the rare CWR species populations is required in the surveyed protected areas. Eight CWR species are recommended for further population genetics studies: Amygdalus nana L., Cerasus fruticosa Pall., Allium rubens Schrad. ex Willd., A. obliquum L., A. schoenoprasum L., Lathyrus gmelinii Fritsch, L. litvinovii Iljin, and L. sylvestris L.